Thermal stability of a eutectic mixture of bis(2, 2-dinitropropyl) acetal and formal: Part A. Degradation mechanisms in air and under nitrogen atmosphere. (July 2016) - Yang, Dali; Pacheco, Robin; Edwards, Stephanie; Henderson, Kevin; Wu, Ruilian; Labouriau, Andrea; Stark, Peter
Abstract: We investigated the chemical and thermal stability of a eutectic mixture of bis(2, 2-dinitropropyl) acetal (BDNPA) and formal (BDNPF) (referred to as NP) in various environments at temperatures below 70 °C. Changes in the chemical composition of samples aged up to two years were characterized using TGA, FTIR, GPC, ESI-MS, and 1 H NMR spectroscopies. The results show that the initial signs of NP degradation can be detected as early as in 12 months at 70 °C in air. The initial step in the degradation is the elimination of HONO molecules, followed by the formation of nitroso-alcohol isomers. While temperature plays a key role in determining the degradation kinetics of the initial stages, the absence or presence of oxygen determines the types and formation rates of various isomers and intermediates during thermal decomposition. In addition, oxygen accelerates the decomposition of the isomers and intermediates, whereas nitrogen has a stabilizing effect. BDNPA shows higher reactivity than BDNPF regardless of the aging conditions, which is attributed to the presence of an extra methyl group in its structure.